Enamel Defects in Maxillary Central Incisors of Infants With Unilateral Cleft Lip - Gomes, Alessandra Cristina [UNESP]; das Neves, Lucimara Teixeira; Gomide, Marcia Ribeiro (Alliance Communications Group Division Allen Press, 2009)
Objective: To evaluate the presence of enamel alterations in deciduous maxillary central incisors of infants with unilateral cleft lip and alveolar ridge, with or without cleft palate, and to compare the occurrence and location of these alterations between the central incisor adjacent to the cleft and the contralateral incisor.Design: Intraoral clinical examination was performed after tooth cleaning and drying by a single examiner with the aid of a dental mirror, dental probe, and artificial light, with the child positioned on a dental chair. The defects were recorded in a standardized manner according to the criteria of the Modified Developmental Defects of Enamel Index.Setting: Hospital for Rehabilitation of Craniofacial Anomalies (HRAC) at Bauru, São Paulo, Brazil.Patients: One hundred one infants were evaluated. All were white, of both genders, aged 12 to 36 months and had at least two thirds of the crowns of maxillary incisors erupted.Results: Demarcated opacity was the most common defect at both cleft and noncleft sides, followed by diffuse opacity. The occurrence of hypoplasia at the cleft side was 11.8%. Most defects affected less than one third of the crown.Conclusion: The occurrence of enamel defects in deciduous maxillary central incisors of patients with unilateral cleft lip was 42.6%, mainly affecting the cleft side as to both number and severity.
Keywords: cleft lip; cleft palate; primary; tooth; tooth abnormalities